Comparison of the effects of puberty counseling for mothers and adolescents on the aggression levels of female adolescents - Fatemeh Torabi; Nezal Azh; Reza Zeighami; Mehdi Ranjbaran (حیات)
Background & Aim: Adolescence is characterized by social, emotional, and physical development, during which aggression emerges as a significant psychological risk factor. This study was designed to compare the effects of puberty counseling for mothers and adolescents on the aggression levels of female adolescents. Methods & Materials: This field trial was conducted with 92 participants divided into three groups: two intervention groups (mothers and adolescents) and one control group. The study was carried out in schools in Qazvin in 2023, with data collected before and after the intervention. Sampling was conducted using a multi-stage random sampling method, and participants were randomly allocated into three groups across six blocks. Each intervention group attended six one-hour face-to-face sessions, while the control group received no intervention. Data were collected using the Novaco Aggression Questionnaire and analyzed with multivariate covariance analysis in SPSS software version 25. Results: The mean aggression scores before the intervention were 50.10±21.68 for the girls’ group, 57.10±93.32 for the mothers’ group, and 54.56±10.61 for the control group (P=0.018). After the intervention, the scores were 37.68±10.16 for the girls’ group, 43.14±76.66 for the mothers’ group, and 49.60±16.11 for the control group, showing a statistically significant difference (P=0.014). Additionally, the intervention had a significant overall effect on reducing the total aggression score (P=0.020), with an effect size estimated at 0.09 based on Partial Eta Squared. Conclusion: The results of this study suggest that puberty education for mothers, as well as for adolescents, can effectively reduce aggression levels in female adolescents.